(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: The incidence of endometrial carcinoma is rising worldwide, partly due to the rising prevalence of obesity. From a diagnostic pathology perspective, it is a heterogeneous disease with a varied range of histomorphological features and is prone to poor interobserver reproducibility. This often has downstream effects on treatment protocols and patient outcomes. The current WHO Classification of Tumors of the Female Genital Tract recommends the incorporation of histology, immunohistochemistry, and molecular testing where possible in the classification of endometrial carcinoma into clinically relevant subtypes. In Kenya, access to ancillary testing is limited and prohibitively expensive, negatively affecting accurate tumor classification. In addition, there are limited local data on the various histologic subtypes of endometrial carcinoma and their respective clinical outcomes. Objectives: To review the classification of endometrial carcinoma as defined by the current WHO Classification contextualized with local clinical, demographic, pathology, and outcome data from two tertiary referral centers in Kenya. Methods: Formalin-fixed paraffin-embedded blocks (FFPE) of 123 cases of endometrial carcinomas between 2012 and 2020 were retrieved from the Aga Khan University and Moi Teaching and Referral Hospitals. The clinical history and follow-up data were abstracted. Hematoxylin and eosin sections were reviewed and 11 immunohistochemical markers (MLH1, MSH2, MSH6, PMS2, ER, PR, ARID1A, P16, PTEN, napsin A, and p53) were determined, and analyzed to arrive at a consensus diagnosis. Results: Six endometrial carcinoma subtypes: endometrioid (68 cases, 55%), serous (32 cases, 26%), carcinosarcoma (15 cases, 12%), clear cell (5 cases, 4%), mixed carcinoma (2 cases, 1.5%), and dedifferentiated carcinoma (1 case, <1%) were reported. The median age of presentation was 63 years (range of 34-90 years) and the median body mass index (BMI) was 27.4 kg/m2. Staging data were available in 95 cases, of which 64 (67%) were in the early stage at presentation. Follow-up data were available in 70 patients with a median follow-up time of 18 months. Recurrences were reported in 11 cases, 5 of which were of the serous subtype. Of the 26 patients whose status was known at the time of the conclusion of the study, 7 died of the disease. Conclusion: To our knowledge, this is the first comprehensive review of the clinical and pathological profiles of various subtypes of endometrial cancer in Kenya with follow-up and outcome data using a wide array of immunohistochemical markers for accurate classification as per the WHO classification.